2017
DOI: 10.1039/c6cc09374d
|View full text |Cite
|
Sign up to set email alerts
|

N-Doped porous carbon nanotubes: synthesis and application in catalysis

Abstract: Uniform N-doped carbon nanotubes were obtained for the first time via a morphology-preserving thermal transformation of organic polymer nanotubes without any additional templates. These carbon nanotubes acted as a superior metal-free carbon catalyst for C-H arylation of benzene, reductive hydrogen atom transfer and oxidation reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…For V‐NCNs‐600, the peak intensity ratio of I D / I G was determined to be 0.81 suggesting a graphitic structure, in agreement with the XRD results (Figure S3) . By comparison, the I D / I G was remarkably increased to 0.95, 0.95 and 0.97 for V‐NCNs‐700, V‐NCN‐800 and V‐NCNs‐900, respectively, indicating an increase in the defect and disorder degree with pyrolysis temperature . Finally, we examined the bulk structure using powder X‐ray diffraction (PXRD, Figure S3).…”
Section: Methodssupporting
confidence: 79%
“…For V‐NCNs‐600, the peak intensity ratio of I D / I G was determined to be 0.81 suggesting a graphitic structure, in agreement with the XRD results (Figure S3) . By comparison, the I D / I G was remarkably increased to 0.95, 0.95 and 0.97 for V‐NCNs‐700, V‐NCN‐800 and V‐NCNs‐900, respectively, indicating an increase in the defect and disorder degree with pyrolysis temperature . Finally, we examined the bulk structure using powder X‐ray diffraction (PXRD, Figure S3).…”
Section: Methodssupporting
confidence: 79%
“…Carbon catalysts have been widely applied in the selective oxidation of alkanes 9 13 , alcohols 14 18 , amines 19 22 , thiols and sulfides 5 , 23 , the nucleophilic addition of alcohol to an epoxide 24 , aldehyde acetalization or esterification 24 , 25 , Michael addition reactions 26 , 27 , F-C addition of indoles to α,β-unsaturated ketones 28 and the synthesis of dipyrromethane 29 , the catalytic reduction of olefin 30 , 31 and nitrobenzene 32 , C-heteroatom coupling reactions 7 , 33 , 34 and heterocycles dehydrogenative aromatization 35 37 , etc.…”
Section: Introductionmentioning
confidence: 99%
“…In an initial set of experiments, 14 selected small organic molecules with nitrogen or oxygen atoms in their structures were tested for the coupling of benzene and iodobenzene according to previous studies and our previous work in this area (as shown in Table 1). 31,[44][45][46][47][48][49] All the tested molecules showed catalytic ability for the conversion except (CH 3 ) 3 OH, which creates extremely large steric hindrance (Table 1, entry 11). Aliphatic diamines exhibited considerable yields, especially aer mono-methylation (Table 1, entries 1-3, 65-71%).…”
Section: Resultsmentioning
confidence: 99%